The Tipperary Duellists or Margate Heroes. - (:unkn) unknown (Fores, S. W., 1790)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Irish Code Duello; Tipperary duellists; Dueling; Margate (England)